2000
DOI: 10.1148/radiographics.20.6.g00nv041551
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive MR Imaging of Acute Gynecologic Diseases

Abstract: Rapid advances in techniques of magnetic resonance (MR) imaging have enabled diagnosis of acute gynecologic conditions, which are characterized by sudden onset of lower abdominal pain, fever, genital bleeding, intraperitoneal bleeding, or symptoms of shock. The chemical-selective fat-suppression technique not only helps establish the characteristics of lesions that contain fat components but also increases the conspicuity of inflammatory lesions. When a T2-weighted image is obtained with a very long effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…T 2 -weighted imaging is a widespread and valuable method used routinely for the diagnosis of many pathologic disorders (1)(2)(3)(4)(5). Information from T 2 -weighted images in terms of pathology is typically analyzed in a qualitative manner by the radiologist by looking at differences in contrast between tissues in one (or two) T 2 -weighted image(s).…”
mentioning
confidence: 99%
“…T 2 -weighted imaging is a widespread and valuable method used routinely for the diagnosis of many pathologic disorders (1)(2)(3)(4)(5). Information from T 2 -weighted images in terms of pathology is typically analyzed in a qualitative manner by the radiologist by looking at differences in contrast between tissues in one (or two) T 2 -weighted image(s).…”
mentioning
confidence: 99%
“…Pregnancy increases tension when the uterus enlarges and alters the anatomical position of an ovarian tumor, and trauma will put pressure on its wall. 6,10,11 An endometrioma may develop adhesions, and changes in position from such dense adhesions and growth of a malignant ovarian tumor could induce spontaneous rupture of the cystic tumor, as noted by Vora's group. 10 In summary, we report a case of ruptured endometrioma associated with an endometrioid adenocarcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies using MR and CT imaging have reported representative features of ovarian rupture to include the absence of a tense, ‰abby, or depressed surface of the cystic lesion. 6,10,11 Cystic ruptured ovarian tumor with hemorrhage can sometimes be detected as well based on a ‰uid-‰uid level in the pelvic space, although this is uncommon because MR imaging of a hemorrhage shows varied signal intensity on T 1 -weighted and T 2 -weighted images. Detection of a ‰uid-‰uid level in the pelvic space enables diagnosis of a ruptured ovarian tumor with greater conˆdence on MR imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential diagnosis of a hemoperitoneum in a patient with cystic ovaries includes ruptured tubal or ovarian pregnancy, ruptured corpus luteum cyst, ovarian endometrioma, and ovarian torsion with hemorrhagic infarction. [8][9][10] In addition, a patient with a ruptured ovarian teratoma can present with a cystic ovarian mass, intraperitoneal free fluid, and clinical signs of peritonitis.…”
Section: Discussionmentioning
confidence: 99%